Cognitive components derived from traditional neuropsychological tests and their associations with plasma p-tau217 and p-tau181 in mild cognitive impairment: a multisite analysis - Ana Perez; Hugo Lewi Hammer; Vebjørn Andersson; Timo Saarinen; Soraya Alfonsín; Guido Maria Giuffrè; Naike Caraglia; Noemi Martellacci; Federico Ramírez-Toraño; Thomas Tveitstøl; Antti Kinnunen; Mia Liljeström; et al. (GeroScience, 2026)
Background Currently, no single biomarker can reliably identify preclinical Alzheimer’s disease (AD), particularly at or before the mild cognitive impairment (MCI) stage. Given the heterogeneity of MCI, integrative approaches are needed to improve early risk stratification. Objectives (i) To derive robust latent cognitive components from a multicenter, clinically defined MCI cohort using principal component analysis (PCA); (ii) to investigate the associations between these components and plasma p-tau217 and p-tau181 levels. Methods Data from 742 MCI participants in the AI-Mind cohort were analyzed. Cognitive domains were derived using PCA with varimax rotation and tested for associations with plasma p-tau biomarkers using site-specific linear regressions, adjusted for age, sex, and education. Results A reproducible four-component cognitive structure emerged (memory, executive/processing speed, verbal fluency, visuospatial ability), with memory as the most p-tau-sensitive domain. The p-tau217 measure showed stronger associations with memory than p-tau181, though effects varied by site. Conclusion The findings indicate that a robust four-factor cognitive structure can be identified in clinically defined MCI cohorts without prior biological selection. The association between latent memory factors and plasma p-tau217, observed primarily in cohorts with higher biomarker burden or clearer amnestic profiles, highlights the potential for blood-based biomarkers to refine risk assessment in routine clinical practice.

Causes of mortality in wild European hedgehog (Erinaceus europaeus) populations in Italy and Switzerland - I. Prandi; E. Dervas; E. Colombino; L. Bertolotti; M. Cardello; D. Ippolito; M. Perotti; M. Vacchetta; S. Zanet; M. Mauthe Von Degerfeld; G. Quaranta; U. Hetzel; et al. (Journal of Comparative Pathology, 2024)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Global warming and human health effects of wood heating life cycle in the Grand-Est region in France - M. Zgheib; G. Quaranta; V. Tschamber; G. Trouvé (Biomass and Bioenergy, 2023)

Correction to: Redescription of the bigeye chimaera, Hydrolagus macrophthalmus de Buen, 1959 (Chondrichthyes: Chimaeriformes), with a genetic characterization of the species - Matthew Jew; David A. Ebert; Jenny M. Kemper; Kristin Walovich; Kimberly L. Quaranta (Marine Biodiversity, 2019)

Redescription of the bigeye chimaera, Hydrolagus macrophthalmus de Buen, 1959 (Chondrichthyes: Chimaeriformes), with a genetic characterization of the species - Matthew Jew; David A. Ebert; Jenny M. Kemper; Kristin Walovich; Kimberly L. Quaranta (Marine Biodiversity, 2019)

Deoxynivalenol content in italian organic durum wheat: Results of a six-year survey - M. Camerini; T. Amoriello; G. Aureli; A. Belocchi; M. Fornara; S. Melloni; F. Quaranta (Cereal Research Communications, 2016)

Use of agro-industrial organic sludge amendment to remediate degraded soil: chemical and eco(geno)toxicological differences between fresh and stabilized sludge and establishment of application rates - Claudete G. Chiochetta; Sylvie Cotelle; Jean-François Masfaraud; Hela Toumi; Gaetana Quaranta; Fabrizio Adani; Claudemir M. Radetski (Environmental Science and Pollution Research, 2016)

Preliminary survey on the co-occurrence of DON and T2+HT2 toxins in durum wheat in Italy - G. Aureli; T. Amoriello; A. Belocchi; M.G. D’Egidio; M. Fornara; S. Melloni; F. Quaranta (Cereal Research Communications, 2015)

Leachates from solid wastes: chemical and eco(geno)toxicological differences between leachates obtained from fresh and stabilized industrial organic sludge - Claudete G. Chiochetta; Luís C. Goetten; Sônia M. Almeida; Gaetana Quaranta; Sylvie Cotelle; Claudemir M. Radetski (Environmental Science and Pollution Research, 2014)

Multiphase Extraction of Light Non-aqueous Phase Liquid (LNAPL) Using Prefabricated Vertical Wells - M. A. Gabr; N. Sharmin; J. D. Quaranta (Geotechnical and Geological Engineering, 2013)

Nasal cytology: the “infectious spot”, an expression of a morphological-chromatic biofilm - M. Gelardi; G. Passalacqua; M. L. Fiorella; A. Mosca; N. Quaranta (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

A new xenicane norditerpene from the Indian marine gorgonian Acanthogorgia turgida - E. Manzo; M.L. Ciavatta; M. Gavagnin; G. Villani; C. Quaranta; L. D'Souza; G. Cimino (Natural Product Research, 2009)

Algorithms to Account for Topographic Shading Effects and Surface Temperature Dependence on Terrain Elevation in Diagnostic Meteorological Models - R. Bellasio; G. Maffeis; J. S. Scire; M. G. Longoni; R. Bianconi; N. Quaranta (Boundary-Layer Meteorology, 2005)

Artificial Insemination Using Local Cattle Breeds in Niger - F. Cristofori; M. Issa; A. Yenikoye; G. Trucchi; G. Quaranta; M. Chanono; C. Semita; H. Marichatou; M. Mattoni (Tropical Animal Health and Production, 2005)

Survey of Ochratoxin A in Cereals from Puglia and Basilicata - M. Muscarella; C. Palermo; T. Rotunno; V. Quaranta; P. D'Antini (Veterinary Research Communications, 2004)

αv Integrins mediate adhesion and migration of breast carcinoma cell lines - Nanette C. Wong; Barbara M. Mueller; Carlos F. Barbas; Pete Ruminski; Vito Quaranta; Emme C. K. Lin; Jeffrey W. Smith (Clinical & Experimental Metastasis, 1998)

Soluble intercellular adhesion molecule-1 in sera from patients with chronic hepatitis C undergoing interferon treatment - A. M. Sonnante; R. Cozzolongo; R. Cuppone; G. De Michele; O. G. Manghisi; M. Quaranta (Archives of Virology, 1997)